Controlled preparation of amphiphilic triblock-copolyether in a metal- and solvent-free approach for tailored structure-directing agents. Issue 18 (8th January 2018) - Balint, Alexander; Papendick, Marius; Clauss, Manuel; Müller, Carsten; Giesselmann, Frank; Naumann, Stefan
Abstract : Organocatalysis is employed as a precise tool for the preparation of triblock-copolyethers for a systematic access to structure-direction. Abstract : Under mild conditions, PPO–PEO–PPO ("reverse Pluronics") and PBO–PEO–PBO copolyether were generated by way of N-heterocyclic olefin-based organocatalysis. Reverse Pluronics with molar masses > 20 000 g mol −1 could be synthesized with excellent control ( Đ M ≤ 1.03) and were converted into (ordered) mesoporous carbons via organic self-assembly to showcase the need for tailor-made copolymer as structure-directing agent.